2008
DOI: 10.1002/ajhb.20757
|View full text |Cite|
|
Sign up to set email alerts
|

Rural urban differences of cardiovascular disease risk factors in adult Asian Indians

Abstract: The prevalence of cardiovascular disease (CVD) risk factors in "People of Indian Origin" (PIO) is exceedingly high and strong relationships among elevated blood pressure, increased levels of lipoproteins, visceral obesity, physical inactivity and subsequent high occurrence of coronary heart disease, type 2 diabetes mellitus etc., were evident in many studies. Increasing urbanization with effective changes in lifestyles could be attributed to explain this exaggerated rate. The present community based cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 26 publications
(28 reference statements)
6
29
4
Order By: Relevance
“…The prevalence of the metabolic syndrome in this study was 35.0%. The high prevalence of metabolic syndrome in Turkmen women was almost in agreement with those of Indian (36.4%) and Taiwanese (36.6%) populations [17]. Differences in the prevalence of metabolic syndrome may depend on age distribution, socioeconomic or nutritional statuses and different ethnic groups.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…The prevalence of the metabolic syndrome in this study was 35.0%. The high prevalence of metabolic syndrome in Turkmen women was almost in agreement with those of Indian (36.4%) and Taiwanese (36.6%) populations [17]. Differences in the prevalence of metabolic syndrome may depend on age distribution, socioeconomic or nutritional statuses and different ethnic groups.…”
Section: Methodssupporting
confidence: 63%
“…Studies which were done on Korean and Taiwanese populations have shown that the prevalences of metabolic syndrome for in women wereas 31.9% and 36.6% [15]. Studies have shown that the prevalence of metabolic syndrome among rural women was 31.25% in Bangladesh and that it was 36.4% in India [16][17]. The prevalence of the metabolic syndrome in this study was 35.0%.…”
Section: Methodsmentioning
confidence: 67%
“…For both genders, urban residents showed higher OR for central obesity, diabetes and dyslipidaemia. Previous studies have documented higher MetS prevalence in the urban v. rural population (29)(30)(31) . Furthermore, these studies showed that rural dwellers had higher diet quality and physical activity than their urban counterparts.…”
Section: Discussionmentioning
confidence: 85%
“…10,42 Yet, studies from neighboring India have reported lower prevalence estimates of low HDL-C values, ranging from 41% to 68%. [43][44][45][46] Among the diet and lifestyle factors investigated, we found that smoking and alcohol consumption were virtually absent in our NNIPS-2 9-to 13-year-old cohort but practiced by *6% and *10%, respectively, among our NNIPS-1 15-to 23-year-old cohort, likely reflecting adoption of these practices through the adolescent years rather than a cohort effect per se. However, neither exposure was associated with cardiometabolic risk after adjustment for potential confounders, possibly due to low numbers of cigarettes and small amounts of alcohol consumed.…”
mentioning
confidence: 81%